Concentración mínima inhibitoria del aceite esencial de Minthostachys mollis “muña” sobre el crecimiento de Listeria monocytogenes y Staphylococcus aureus - Mantilla German, Susana Fiorella (2018)
The control of microbial growth is an important factor in food preservation, for which chemicals are commonly used; however, these are being replaced by natural substances such as essential oils. The objective of the present investigation was to determine the minimum inhibitory concentration of the essential oil of Minthostachys mollis "muña" on the growth of Listeria monocytogenes and Staphylococcus aureus. To do this, the essential oil was extracted from the entire muña plant using the steam distillation technique, and a stock solution was prepared. The growth curve of L. monocytogenes and S. aureus was determined, determining that the generation time was 55 and 42 minutes respectively; and the logarithmic phase averages 11 and 8 hours respectively. The inoculum of each bacterium was prepared, in its average logarithmic phase and with the stock solution the determination of the minimum inhibitory concentration was made, using microculture wells with final concentrations of 320; 160; 80; 40; twenty; 10; 5 and 2.5 μg/mL of the essential oil. The systems were incubated at 37°C for 24 hours, everything was done in triplicate. The result of the minimum inhibitory concentration of Minthostachys mollis "muña" on the growth of L. monocytogenes and S. aureus was 40 μg/mL and 80 μg/mL respectively.